# What is the final step in solving the inequality -2(5 - 4x) < 6x - 4?

x < - 3, x > - 3, x < 3, x > 3

**Solution:**

Given: Inequality is -2(5 - 4x) < 6x - 4

Solve the system of linear inequalities using the following steps:

**Step 1: **First solve the bracket.

⇒ -10 + 8x < 6x - 4

**Step 2:** Add 10 on both sides.

⇒ -10 + 8x + 10 < 6x - 4 + 10

⇒ 8x < 6x + 6

**Step 3: **Subtract 6x from both sides.

⇒ 8x - 6x < 6x + 6 - 6x

⇒ 2x < 6

**Step 4: **Divide both sides by 2

⇒ 2x/2 < 6/2

⇒ x < 3

## What is the final step in solving the inequality -2(5 - 4x) < 6x - 4?

x < - 3, x > - 3, x < 3, x > 3

**Summary:**

The final step in solving the inequality -2 (5 - 4x) < 6x - 4 is x < 3.